Women's Rights as Human Rights: A Critique of the Patriarchal Perspective in the Legal System and Its Implementation in Indonesia - Ghina Angelina Quraeny; Muhammad Ramadhan (Program Pascasarjana UIN Sumatera Utara Medan, 2022)
Women's rights constitute an inseparable part of human rights and are recognized in both Islamic teachings and international human rights instruments. Islam upholds the principles of justice, equality, freedom, and mutual respect, affirming that all human beings are equal before Allah, with piety serving as the only measure of distinction. Despite these principles and the existence of numerous international conventions and national legal frameworks, women continue to experience discrimination, violence, and unequal access to political, economic, educational, and social opportunities. This study aims to examine women's rights from the perspectives of Islamic law and the Indonesian legal system while identifying the challenges that hinder the effective realization of gender equality. The research employs a normative juridical approach using descriptive-analytical methods. Data were collected through library research by analyzing primary legal materials, including the 1945 Constitution of the Republic of Indonesia, Law Number 39 of 1999 concerning Human Rights, Law Number 23 of 2004 concerning the Elimination of Domestic Violence, the Universal Declaration of Human Rights (UDHR), the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), and relevant secondary sources such as books and scholarly journals. The findings reveal that Indonesia has established a comprehensive legal framework to protect women's rights in areas such as politics, citizenship, education, employment, health, legal capacity, and marriage. However, the implementation of these legal protections remains constrained by deeply rooted patriarchal culture, gender stereotypes, institutional barriers, socio-economic inequality, and limited political participation. Moreover, the traditional human rights approach often fails to adequately recognize violence occurring within the domestic sphere as a human rights issue. Therefore, strengthening legal enforcement, promoting gender-sensitive public policies, enhancing women's empowerment, and transforming patriarchal cultural values are essential to ensuring the effective protection and fulfillment of women's rights. These efforts are necessary to achieve substantive gender equality and uphold human dignity in accordance with both Islamic principles and universal human rights standards.